The Power Load Model for Electric Vehicle Charging Modelling and its Utilisation for Voltage Level Studies and Cables Ampacity in Distribution Grid - Síťař, Vladislav; Vysloužil, Tomáš; Raková, Lenka; Hruška, Tomáš (Manufacturing Technology Journal, 2021)
When electrical energy is drawn by electric vehicles from charging stations at charging process the voltage drops and increased current loading of cable lines in distribution grid occur. Inasmuch the electrical grid is insufficiently dimensioned or at large amount electric vehicles concurrently charges without controlled charging system, the voltages could decrease under desired level in grid points. This leads to the deterioration of voltage quality in given grid. The higher cables current loading leads to active power losses increase and decrease their service life. The paper describes the utilisation of modelling the electric vehicles when charging by power load model in physical diagram implemented into alternative simulation software. The created charging station load model is used for solving of voltage studies in distribution grid and for the analysis of cable lines ampacity. The grid contains a small number of points and low penetration of charging stations. Voltage levels are solved when random operation of charging stations during the working day without controlled system. For other loads, the typified daily loads diagrams of households are used.
Keywords: Electric Vehicle Charging; Electric Vehicle Charging Modelling; Voltage Level; Cables Ampacity; Typified Daily Load Diagram